Hydrodynamics of spur and groove formations on a coral reef. Issue 6 (19th June 2013) - Rogers, Justin S.; Monismith, Stephen G.; Feddersen, Falk; Storlazzi, Curt D.
Abstract : [1] Spur and groove (SAG) formations are found on the fore reefs of many coral reefs worldwide. Although these formations are primarily present in wave‐dominated environments, their effect on wave‐driven hydrodynamics is not well understood. A two‐dimensional, depth‐averaged, phase‐resolving nonlinear Boussinesq model ( funwaveC ) was used to model hydrodynamics on a simplified SAG system. The modeling results show that the SAG formations together with shoaling waves induce a nearshore Lagrangian circulation pattern of counter‐rotating circulation cells. The mechanism driving the modeled flow is an alongshore imbalance between the pressure gradient (PG) and nonlinear wave (NLW) terms in the momentum balance. Variations in model parameters suggest the strongest factors affecting circulation include spur‐normal waves, increased wave height, weak alongshore currents, increased spur height, and decreased bottom drag. The modeled circulation is consistent with a simple scaling analysis based on the dynamical balance of NLW, PG, and bottom stress terms. Model results indicate that the SAG formations efficiently drive circulation cells when the alongshore SAG wavelength allows for the effects of diffraction to create alongshore differences in wave height without changing the mean wave angle. Key Points: Waves induce circulation cells on spur and groove formations Simple scaling predicts how circulation varies w/ wave ht., etc. Circulation is efficient when diffraction causes alongshore wave ht variation